Enhancing sustainable progress: an analysis of supreme audit institutions' performance audits and information disclosure practices - Dionisijev, Ivan; Bozhinovska lazarevska, Zorica (Emerald, 2024)
PurposeThis technical paper has two purposes. It firstly aims to explore Supreme Audit Institutions' information disclosure of Sustainable Development Goals’ related performance auditing practices by focusing on four Balkan countries: Croatia, Montenegro, North Macedonia, and Slovenia. Secondly, it aims to investigate whether membership in the European Union, in conjunction with the adoption of unified EU legislation and best practices in socio-economic and political spheres, influences the level of disclosure practices in SDGs’ auditing and the national approaches to auditing SDG-related topics.Design/methodology/approachThe study employs a content analysis approach to examine the annual reports of SAIs as government audit bodies in the aforementioned countries. The analysis focuses on the disclosure of SDGs’ information and the level of performance auditing conducted concerning the SDGs. Furthermore, the study utilizes the Spearman rank-order correlation test to explore whether membership in the European Union influences the frequency of SDG-related audits and the amount of information disclosed.FindingsThe findings highlight that the Slovenian SAI stands out for its comprehensive information disclosure in annual reports related to SDGs or sustainability reporting. It also demonstrates a high level of performance auditing on SDG topics. Following closely are the Macedonian and Croatian SAIs, which also exhibit noteworthy performance in these areas. In contrast, the Montenegrin SAI displays the lowest level of information disclosure and has conducted fewer performance audits related to SDGs. Furthermore, the study reveals that there is no significant correlation between EU membership and the extent of SDG disclosure in the SAIs' annual reports and the level of performance auditing.Research limitations/implicationsIt is important to acknowledge that this study is limited in scope, focusing solely on the annual reports of SAIs in four countries. Additionally, the research does not explore the fundamental factors that contribute to the variations in SDG auditing levels among SAIs.Originality/valueThis paper contributes to the expanding literature on the implementation and monitoring of the SDGs by providing valuable insights into the extent of SDG-related performance auditing conducted by SAIs and the level of information disclosure within their annual reports. The findings have implications for policymakers, auditors, and other stakeholders involved in fostering sustainable development practices and accountability mechanisms.
Keywords: Sustainable Development Goals; Supreme Audit Institutions; Performance Auditing; Balkan Counties